Non-syndromic Bilateral Branchial Cyst: A Case Report - Nor Azirah Salahuddin; Saravana Selvi Sanmugam; Azreen Zaira Abu Bakar; Siti Asmat Md Arepen; Nour Hanan Daniah Mohd Bakhit; Ahmad Anwaar bin Muhammad Saifullah; Nor Eyzawiah Hassan (Oman Medical Specialty Board, 2024)
Indexed by Scopus